(3GdJPcQI GdMeOhfjIs - (3eMeO Hf GdMSf Hf eMeO Hf Ydj Hf MeOhf, CHh GdeYGdj, HgGA GdOjf GdHZOGOj,J (B562 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg jHOC GdehLhO efg HNWHI GdfHi Udi Gddg Ydjg hSde Mjf JRhL aGWeI YdjgG GdSdGe s
(3BNQgG (B:s
(3ade jROg Ydi GdfHGM MJi jFS efg aJQcg jJdhg HGH GdcfGjI hGdJYQjV hGdJhQjI hGdCMGLi hGdESJWQGA s
(3LRA efgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B217s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs